The Influence of Service Quality and Price on Satisfaction Through Brand Image (Case Study of Students of the Faculty of Economics and Business, PGRI University, Semarang, 2023) - Felicia, Dea; Kurniawan, Bayu; Goeltom, Henry Casandra (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the effect of service quality and price on satisfaction through brand image on students of the Faculty of Economics and Business, PGRI University, Semarang in 2023. Data were collected through a survey with 315 respondents. Researchers used primary data obtained from distributing questionnaires via Google Form to students of the Faculty of Economics and Business, PGRI University, Semarang. The technique used in sampling is non-probability sampling. The respondents were students of the Faculty of Economics and Business, PGRI University, Semarang in 2023. The results of this study are that service quality and price have a significant effect on student satisfaction, service quality and price have a significant effect on brand image, brand image has a positive and significant effect on student satisfaction, service quality a significant effect on student satisfaction with brand image as an intervening variable, and price have a significant effect on student satisfaction with brand image as an intervening variable. Keywords: Service quality, Price, Satisfaction, and Brand Image